The Level of the English Proficiency Affecting the Academic Performance of the Freshmen College Students at Gordon College, Olongapo City - Panado, Ana Lee M. (Future Science / FSH-PH Publications, 2023)
The objective of the study is to determine the level of proficiency in the four English language skills of freshmen students of selected courses at Gordon College and established its relationship to academic performance. The design used was descriptive method with the questionnaire as the main instrument in gathering the data. The researcher devised new research questionnaire that would suit to present study. The researcher made a 50-item English Proficiency Test which covered the four language skills in English which are reading, listening, writing, and grammar. It was concluded that: 1. Typical freshman student-respondent is a female, 17 years old, whose parent is college graduate or a college undergraduate, enrolled as BSHRM, BCSC/IT or BSBA and products of private or public high schools. 2. The level of performance of a student-respondent in reading is excellent (10.27), in listening (8.33) and writing (8.1) above average and in grammar (7.69) average. 3. The academic performance in English is above average. 4. There is significant difference in the level of proficiency of student-respondents in the four (4) language skills. 5. There is significant difference in the level of proficiency in the four (4) language skills when respondents are grouped according to age, course, parent’s highest educational attainment and type of high school graduate from but no significant difference when grouped according to sex. 6. There is significant relationship between the level of performance in the four (4) language skills and academic performance in English subjects of the student-respondents.